Parent‐delivered contingency management for a treatment‐refusing young adult with gaming disorder: Case report. Issue 3 (1st January 2022) - Riley, Ben J.; Baigent, Michael; Battersby, Malcolm W.; King, Daniel L.
Abstract: Online video gaming is a popular activity among people of all ages. For some, however, gaming can become problematic. While evidence exists for the effectiveness of cognitive behavioural therapy for gaming disorder (GD), a major challenge is that adolescents and young adults, particularly males, are often reluctant to seek help and engage long term with a mental health practitioner. This report presents a case involving brief parent‐delivered contingency management for a 19‐year‐old male with GD who refused to engage with treatment services following a significant decline in functioning and a high‐lethality suicide attempt. This approach led to a substantial reduction in gaming time, as well as related gains in self‐care and independence. This case highlights the value and feasibility of developing a therapeutic alliance with a parent to manage excessive gaming behaviours among treatment‐refusing individuals with GD. Practical challenges and associated lessons from managing this case are discussed. Practitioner points Brief parent‐delivered contingency management was implemented for a 19‐year‐old treatment‐refusing male with GD. This approach led to a substantial reduction in the young man's gaming time as well as related gains in areas of self‐care and independence at 6‐month follow‐up. This case highlights the value and feasibility of developing a therapeutic alliance with a parent to manage excessive gaming behaviours among treatment‐refusing individuals with GD.